1979
DOI: 10.1172/jci109489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Renal Mass and Dietary Protein Intake on Amino Acid Release and Glucose Uptake by Rat Muscle In Vitro

Abstract: A B S T R A C T Epitrochlearis musclesTyrosine (TYR) and phenylalanine (PHE) release rates also were increased in muscles from Nx rats compared with C after 1 h of incubation. Release rates were highest in the Nx group fed 10% casein and decreased with increasing protein intake. Addition of insulin decreased the release rates of Nx rats to C values in each group. After 3 h of incubation, release rates of TYR and PHE in muscles from Nx rats remained significantly above C values for all groups, but responded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

1981
1981
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…Garber reported that alanine and glutamine release from muscle of fed CRF rats was increased and that radiolabeled leucine incorporation into muscle protein was decreased, which suggested that both protein degradation and synthesis were abnormal in CRF (18). Harter et al compared net protein degradation rates in epitrochlearis muscles from uremic and control rats fed different levels of protein (2). At each level of dietary protein, net protein degradation was higher in CRF rats; the difference was greatest when 10% protein was fed even though the degree of azotemia was least in this group of rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Garber reported that alanine and glutamine release from muscle of fed CRF rats was increased and that radiolabeled leucine incorporation into muscle protein was decreased, which suggested that both protein degradation and synthesis were abnormal in CRF (18). Harter et al compared net protein degradation rates in epitrochlearis muscles from uremic and control rats fed different levels of protein (2). At each level of dietary protein, net protein degradation was higher in CRF rats; the difference was greatest when 10% protein was fed even though the degree of azotemia was least in this group of rats.…”
Section: Discussionmentioning
confidence: 99%
“…At each level of dietary protein, net protein degradation was higher in CRF rats; the difference was greatest when 10% protein was fed even though the degree of azotemia was least in this group of rats. It is possible that the adverse effect of the 10% protein diet was the result of an inadequate protein intake, since at most 10 g of food was allowed each day and the average weight of both CRF and control rats decreased (2,9). When CRF rats were given more protein, which lead to more severe azotemia, it is possible that these rats were acidotic, and that this contributed to the significant increase in net protein degradation compared with that in muscles of control rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skeletal muscle preparations from rats made chronically uremic by surgery release large quantities of alanine and glutamine in vitro. This appears to result, in part, from an increased rate of protein degradation in muscles from uremic animals (10,11). Since both chronic renal insufficiency and hyperparathyroidism are associated with substantial elevations in the circulating levels of parathyroid hormone, and since both disease states have a significant muscle dysfunction and wasting disorder associated with them, a relationship between the elevated levels of parathyroid hormone and the disordered skeletal muscle metabolism of both disease complexes seems possible.…”
Section: Introductionmentioning
confidence: 99%